Mass media of national minorities as a means of national reconciliation in society - Matviienkiv, Svitlana; Shmalenko, Iuliia (Studia Europaea Gnesnensia, 2022)
This paper examines how the presence the media of national minorities aligns itself with the principles of civil society principles and fosters tolerance and stability in the Ukrainian multi-ethnic society. It follows from the analysis that the existence of periodicals published by national minorities increases social awareness, contributes to national reconciliation, mutual understanding between people, and promotes social development. It was found that ongoing publication of national periodicals approved by the state enables representatives of national minorities to feel equal citizens of Ukraine, whose high social status and cultural needs are acknowledged and recognized. The registered periodicals and radio broadcasts of the Polish national minorities in the Carpathian region evince the existence of free non-governmental organizations that reflect the interests of social groups and their values. It is emphasized that the Polish community of Prykarpattia is dispersed, therefore the development trend of its social media reflects the nationwide progress of ethnic integration of particular national communities into society. Also, the authors show that Polish-language and bilingual newspapers and magazines of the Ivano-Frankivsk region are important factors in the preservation and public expression of the identity of national minorities, reflect their unique culture, traditions and the degree of their assimilation.